2020
DOI: 10.3390/ijms21113900
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Related Cutaneous Adverse Events in Philadelphia Chromosome-Negative Myeloproliferative Neoplasms: A Literature Review

Abstract: Since myeloproliferative neoplasms (MPN) pose a significant risk for vascular and thrombotic complications, cytoreductive therapies, such as hydroxyurea (HU), interferon (IFN) inhibitors, and Janus kinase (JAK) inhibitors are recommended for patients at high risk. However, these agents also place patients at increased risk for drug-related cutaneous adverse events. Herein, we review the literature on skin toxicity related to the use of drugs for the treatment of MPN. Overall, the cytoreductive agents used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 90 publications
0
17
0
Order By: Relevance
“…203 Among these reactions, which have been reported in 7% to 89% of patients, the most common is a maculopapular rash ($67%) ranging from mild to severe erythroderma/exfoliative dermatitis. [204][205][206] Imatinib was the culprit in nearly 10% of lichenoid adverse reactions of the skin and oral mucosa, described as similar to lichen planus on histopathologic analysis (Figure 2), but may also exhibit eosinophils in the cellular infiltrate, focal parakeratosis, and deep perivascular inflammation. [207][208][209][210][211] One patient had a pruritic eruption with large, hyperchromatic, epidermotropic lymphocytes along with superficial and mid-perivascular inflammation, raising the possibility of mycosis fungoides.…”
Section: Cdk4/6 Inhibitorsmentioning
confidence: 99%
“…203 Among these reactions, which have been reported in 7% to 89% of patients, the most common is a maculopapular rash ($67%) ranging from mild to severe erythroderma/exfoliative dermatitis. [204][205][206] Imatinib was the culprit in nearly 10% of lichenoid adverse reactions of the skin and oral mucosa, described as similar to lichen planus on histopathologic analysis (Figure 2), but may also exhibit eosinophils in the cellular infiltrate, focal parakeratosis, and deep perivascular inflammation. [207][208][209][210][211] One patient had a pruritic eruption with large, hyperchromatic, epidermotropic lymphocytes along with superficial and mid-perivascular inflammation, raising the possibility of mycosis fungoides.…”
Section: Cdk4/6 Inhibitorsmentioning
confidence: 99%
“…Undoubtedly, one of the most evident links between MPNs and SC is the cytotoxic effect of treatment [ 4 , 5 , 13 ]. In 2019, an international nested case–control study (involving 30 centers) was conducted, aiming to evaluate the risk of SC after exposure to cytoreductive drugs, in a cohort of 1881 Philadelphia-negative MPNs [ 4 ].…”
Section: Possible Links Between Mpns and Scmentioning
confidence: 99%
“…Eight out of 10 studies reported an association between HU and NMSC [ 7 , 11 , 15 - 18 , 20 , 22 ]. Two studies found no statistical significance between HU and the development of secondary solid cancers (including cutaneous malignancies) [ 19 , 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…Antonioli et al described worsening of lesions and progression to SCC on continuing the HU treatment in three patients [ 15 ]. These cancers are predominantly seen on the scalp, ears, neck, hands, and feet [ 15 - 18 , 22 ]. This shows that excessive exposure to sunlight may play a contributory role in carcinogenesis.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation